2001
DOI: 10.1002/tea.10008
|View full text |Cite
|
Sign up to set email alerts
|

Fostering students' knowledge and argumentation skills through dilemmas in human genetics

Abstract: This study examined the outcomes of a unit that integrates explicit teaching of general reasoning patterns into the teaching of a specific science content. Specifically, this article examined the teaching of argumentation skills in the context of dilemmas in human genetics. Before instruction only a minority (16.2%) of the students referred to correct, specific biological knowledge in constructing arguments in the context of dilemmas in genetics. Approximately 90% of the students were successful in formulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
748
4
131

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,054 publications
(976 citation statements)
references
References 24 publications
49
748
4
131
Order By: Relevance
“…Results from the study reported in Mercer et al (2004) suggest that exploratory talk, or the discursive practice in which students express and collaboratively explore their opinions through a systematic and joint reasoning, has an impact on secondary students' science learning and reasoning skills. In addition, results from four studies with primary (Che & She, 2012) and secondary students (Venville & Dawson, 2010;Wilson et al, 2010;Zohar & Nemet, 2002) support this conclusion. However, there are uncertainties about how these results should be interpreted.…”
Section: Argumentation For Science Learningsupporting
confidence: 69%
See 1 more Smart Citation
“…Results from the study reported in Mercer et al (2004) suggest that exploratory talk, or the discursive practice in which students express and collaboratively explore their opinions through a systematic and joint reasoning, has an impact on secondary students' science learning and reasoning skills. In addition, results from four studies with primary (Che & She, 2012) and secondary students (Venville & Dawson, 2010;Wilson et al, 2010;Zohar & Nemet, 2002) support this conclusion. However, there are uncertainties about how these results should be interpreted.…”
Section: Argumentation For Science Learningsupporting
confidence: 69%
“…Although there is scarce research testing these benefits, some empirical evidence on peer interactions partially supports it (Asterhan & Schwarz, 2007Howe et al, 2007). Some studies have tested the effect of the argumentative type of whole-class talk on learning, but they are only partially conclusive and do not prove the effect of the discussion of contradictory ideas (Che & She, 2012;Mercer, Dawes, Wegerif, & Sams, 2004;Venville & Dawson, 2010;Wilson, Taylor, Kowalski, & Carlson, 2010;Zohar & Nemet, 2002). Considering that whole-class interactions are the most frequent ones in classrooms around the world (Howe, 2010), it is relevant to investigate the effect of whole-class discussion on learning.…”
mentioning
confidence: 99%
“…Recent studies involving example cases of genetically modified foods (Walker & Zeidler, 2003), human genetic engineering Zohar & Nemet, 2002), animal experimentation (Simonneaux, 2001;Zeidler et al, 2002), and environmental dilemmas (Hogan, 2002;Kolstø, 2001b) provide strong support for the efficacy of using controversial socioscientific case studies to foster critical thinking skills and moral and ethical development. These studies strongly suggest that curricula using such issues provide an environment where students become engaged in discourse and reflection that affect cognitive and moral development.…”
Section: Thematic Areas Of Recent Research Connected To Ssimentioning
confidence: 99%
“…Argumentation refers to the process of proposing, supporting, criticizing, evaluating, and competing ideas using evidence, critical thinking and rationality (Kuhn, 1993). Proponents of argumentation maintain that argumentation based instruction is effective in promoting students' understanding of the nature of science (Sandoval & Millwood, 2005;Simon et al, 2006) and their conceptual understanding of core scientific ideas (Duschl & Osborne, 2002;Erduran & Jimenez-Aleixandre, 2008;Jimenez-Aleixandre, Rodriguez, & Duschl, 2000;Sampson & Clark, 2008;von Aufschnaiter, Erduran, Osborne & Simon, 2008;Zohar & Nemet, 2002). These scholars maintain that © 2013 iSER, Eurasia J.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, research on argumentation in science education has intensified exponentially within the last decade (Bricker & Bell, 2008;Duschl & Osborne, 2002;Erduran & Jimenez-Aleixandre, 2008;Kelly & Chen, 1999;Sandoval & Millwood, 2008;2005;Sampson & Clark, 2008;Simon, Erduran & Osborne, 2006;Zohar & Nemet, 2002). Argumentation refers to the process of proposing, supporting, criticizing, evaluating, and competing ideas using evidence, critical thinking and rationality (Kuhn, 1993).…”
Section: Introductionmentioning
confidence: 99%